Bahasa sarkasme netizen dalam komentar akun instagram Inara Rusli Bulan Juni 2023 - Fikriyah, Mumtazatul (Universitas Lampung, 2024)
The use of technology is increasingly sophisticated in the current era of globalization. Utilizing Instagram as a social networking platform is one of them. Instagram is a social networking platform where users share information freely and quickly. Of course, the use of social media has negative impacts. One of his weaknesses is his tendency to use sarcasm, which can result in rudeness. The definition of sarcasm is emitting a sharp feeling directed at something. The topic of this research is sarcasm comments on Instagram accounts. Finding out how often sarcasm is used on social media is the aim of this research. The target of this research study is the comments column on Inara Rusli's Instagram account in the period June 2023 which contains language that is inappropriate for netizens to use. A descriptive qualitative approach was used in this investigation. The data collection technique for this research is to listen to and record netizen comments that violate the principles of linguistic politeness. Based on research findings, 9 data on sarcasm language used by netizens in comments on Inara Rusli's Instagram account for the period June 2023 were found. This data includes 3 data on violations of the policy maxim, 3 data on violations of the maxim of sympathy, and 3 data on violations of the maxim of appreciation. Violations of this maxim are also characterized by sarcasm which aims to insult, bring down other people, and ridicule people.Keywords: sarcasm, netizen comments, instagram